Analisis Perbedaan Tarif Riil Rumah Sakit Dengan Tarif INA CBG’S Di Rumah Sakit X Ponorogo Pada Semester Pertama Tahun 2024 - Sunayya, M. Mustamik (Universitas Pahlawan Tuanku Tambusai, 2024)
Health insurance in Indonesia uses the Diagnosis Associated Group (DRG) or INA CBG's payment system to improve efficiency and access to health services. However, there is a problem of differences in rates between those set by hospitals and the INA CBG's system, which is experienced by RSU X Ponorogo. This hospital serves most JKN patients and faces challenges in financial management and service quality due to the difference in rates. This study aims to identify tariff challenges and provide recommendations for improving the efficiency of health services. This retrospective descriptive study used secondary data from BPJS patient inpatient claims from January to June 2024. A total of 5,319 claims were described, and the results showed that the Internal disease group claimed the most claims and the largest negative difference, followed by Heart and Lung diseases. Although some disease groups such as Children and Urology recorded positive differences, most diseases experienced significant negative differences. The most claims came from the elderly with a negative difference of 50.06%. In conclusion, rates need to be adjusted to real costs, resources optimized, and treatment protocols more efficient to improve hospital visits and health service quality.